2023
DOI: 10.1037/lat0000220
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of ethnic–racial socialization and parental warmth on Latinx youth psychosocial outcomes.

Abstract: Cultural socialization and preparation for bias messages are the two most studied dimensions of ethnic-racial socialization, although among Latinx samples, preparation for bias has received significantly less research attention (Ayo ´n et al., 2020). While research suggests that cultural socialization fosters positive youth development, the effects of preparation for bias are much more equivocal (Umaña-Taylor & Hill, 2020). We extended this line of research by testing whether parental warmth moderated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Our last question focused on the indirect effects between ERS messages and internalizing symptoms. Given prior studies that have identified a negative relation between cultural socialization and mental health indicators among Latinx youth (e.g., Espinoza et al., 2016; Salcido & Stein, 2023), we examined one possible mechanism through which cultural socialization may relate to mental health. Controlling for frequency of discrimination, we found that cultural socialization was directly related to the use of proactive coping strategies 6 months later, which in turn, was related to fewer symptoms of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our last question focused on the indirect effects between ERS messages and internalizing symptoms. Given prior studies that have identified a negative relation between cultural socialization and mental health indicators among Latinx youth (e.g., Espinoza et al., 2016; Salcido & Stein, 2023), we examined one possible mechanism through which cultural socialization may relate to mental health. Controlling for frequency of discrimination, we found that cultural socialization was directly related to the use of proactive coping strategies 6 months later, which in turn, was related to fewer symptoms of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that ERS practices relate to youth mental health outcomes among Latinx samples. For instance, cultural socialization has been related to higher self‐esteem (e.g., Gonzales‐Backen et al., 2017; Salcido & Stein, 2023) and decreases in depressive symptoms (e.g., Espinoza et al., 2016; Wang & Benner, 2016). Findings with preparation for bias are more equivocal (e.g., Salcido & Stein, 2023), but this may be due to limited studies examining preparation for bias among Latinx families (Ayón et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation